The Nexus of Self-Efficacy and Career Planning on the Work Readiness of Fresh Graduates in Semarang City - Eva Saputri; Mochamad Purnomo (Universal Business and Management Review, 2025)
This study aims to examine the influence of self-efficacy and career planning on the work readiness of fresh graduates in Semarang City. The type of research used is a quantitative research method. The population in this study consisted of fresh graduate students from the Faculty of Economics and Business, Universitas Wahid Hasyim, Indonesia, class of 2020, with a sample of 76 respondents. The sampling technique applied was non-probability sampling. Data were collected through questionnaires. The data analyzed using the IBM SPSS version 22 application with multiple linear regression analysis methods. The results of the partial test self-efficacy does not have a significant effect on student work readiness, while career planning has a positive and significant effect on student work readiness. This study concludes that self-efficacy and career planning simultaneously have a positive and significant effect on student work readiness.